Contemporary Criminal and Criminal Executive Law Conflicts and Ways of Overcoming Them - Epikhin, Alexander Yuryevich; Zaitsev, Oleg Aleksandrovich; Tasakov, Sergei Vladimirovich; Nechaeva, Elena Vladimirovna; Mishin, Andrey Viktorovich (Cuestiones Políticas, 2020)
The article discusses the definition and correlation of the concepts of "conflict" and "competence" and provides various expert opinions on this. In the methodology it is an analytical research based on documentary. In modern scientific literature, the clash of the rules of criminal law is called conflict of laws, using the definitions indicated as identical concepts. However, the authors point to the controversial nature of such an interpretation of those concepts.  The causes of conflicts in the rules of Russian law are analyzed.  Thereis also a detailed analysis of conflicts in the rules of domestic criminal law and criminal executive law. In the context of the topic studied, the authors refer to the categories of criminal law and criminal executive law as the principles of criminal law. It emphasizes by way of conclusion that the conflicts identified are not an exhaustive list, simply the authors of this work managed to consider only some aspects of the subject, therefore the conclusions and suggestions are not indisputable. In any case, the discussion of these issues is important to achieve coherence in the rules of criminal law and criminal executive law.